Unveiling Public Perspectives on Domestic Violence in Indonesia: A Multi-Platform Social Media Analysis - Anggranerista, Bektiana Sungsang; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This research investigates public sentiment among Twitter users regarding domestic violence. To comprehensively capture this sentiment, the study employs a broad approach to data collection across various social media platforms, focusing on a specific timeframe from October 6th to October 12th, 2023. Methodology: The methodology involves searching blogs using relevant keywords and analyzing images from Flickr with appropriate tags. On forums such as Reddit or Quora, the search targets relevant threads within the specified period. Results: Google+, despite its inactive status, is accessed via search with a date filter. News data is gathered through news finders by adjusting dates to note sources, titles, and key quotes. Newsletter archives are searched on dedicated websites, while podcasts are identified through popular platforms, noting titles and details. TikTok data is collected using hashtags or keywords, and Twitter Applications/Originality/Value: the focal point of the study, is explored for tweets and threads related to domestic violence, recording usernames, tweets, and relevant responses. YouTube videos are also searched for relevant content.